The Effect of the Use of Problem Based Learning (PBL) Based on Student Worksheets (LKPD) on the Mastery of Science Concepts in Class V Ecosystem Materials - Dewi Suhandary; Atikah Syamsi; Heru Mudiyanto (Indonesian Journal of Elementary Education (IJEE), 2024)
The background of this research is that there is no influence on the use of teaching materials in accordance with curriculum provisions, target characteristics, and problem solving demands and the application of the Problem Based Learning (PBL) model provided by teachers in learning has not been fully listed to increase students' understanding. The purpose of this study was to determine the effect of Problem Based Learning (PBL) student worksheets on Ecosystem Component Material by utilizing scientific literacy on ecosystem material (water cycle) at SDN Cipedak 05 Pagi, South Jakarta. The research method used is the experimental method with the approach used in this study is a quantitative approach. The form of the design is "pre-test and post-test one group design". The results of the study showed the following: 1) Using the PBL-based LKPD showed a result of 85 with a good category or predicate value B. 2) Mastery of the Natural Science concept with a high tendency of 6 people or 18.8%, medium category of 21 people or 65.6% and the low category is 5 people or 15.6%. Thus it can be concluded that the mastery of the science concept in class V SDN Cipedak 05 Jakarta, is classified as the medium category. 3) In the Discussion there is a sig.(2-tailed) value of 0.000 <0.05. it was concluded that Ha was accepted, so that there was a significant influence on the use of Student Worksheets (LKPD) Based on Problem Based Learning (PBL) on the mastery of the science concept in class V students at SDN Cipedak 05 Pagi Jakarta.Keywords: Student Worksheets, Project Based Learning, Science Concepts